Key descriptors for Sclerocarya birrea (marula) - Chege, J.; Muchugi, A.; Nyoka, B.I.; Kang’ethe, S.; Jamnadass, Ramni; Cognetti de Martiis, S.; Cerutti, A.L.; Alercia, A. (ICRAF and FAO, 2021)
This Descriptor list consists of an initial minimum set of characterization and evaluation descriptors for Sclerocarya birrea. This strategic set aims at facilitating access to and utilization of this African indigenous fruit tree. It does not exclude the addition of other descriptors at a later date. The strategic set of data standards is designed to facilitate access to and utilization of plant genetic resources for food and agriculture information. Together with passport information, descriptors are critical to the effective sharing of characterization and evaluation data and to the efficient use of plant genetic resources for food and agriculture.